Precipitation determines the magnitude and direction of interannual responses of soil respiration to experimental warming - Wang, Yonghui; Song, Chao; Liu, Huiying; Wang, Shiping; Zeng, Hui; Luo, Caiyun; He, Jin-Sheng (Plant and soil, 2021)
Background and aims Soil respiration (R s ) is expected to positively feedback to climate warming. The strength of this feedback is uncertain as numerous environmental factors, such as precipitation and soil moisture, can moderate the warming response of R s . Methods We combined seven-year R s measurements in a warming experiment in the Tibetan alpine grassland with a meta-analysis on grassland warming experiments globally to investigate how precipitation and soil moisture influences the warming response of R s . We further analyzed the warming responses of heterotrophic (R h ) and autotrophic (R a ) components of R s . Results Warming enhanced growing-season R s in the wet years but decreased it in the dry years in the field experiment at the Tibetan grassland. Precipitation modulated the warming responses of growing-season R s via R h , but not R a . Consistent with the field experiment, a positive relationship between precipitation and the warming response of growing-season R s was also observed in the global-scale meta-analysis on grassland warming experiments. Conclusions Precipitation influences the warming effects on R s and could result in variation in warming response of R s across years and experimental systems. Empirical functions provided by this study could be used to reduce the uncertainty in predicting R s in a warmer future.